2016
DOI: 10.1177/1076029616655617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of VKORC1 and CYP2C9 Polymorphisms on Daily Acenocoumarol Dose Requirement in South Indian Patients With Mechanical Heart Valves

Abstract: Presence of a mutant allele of VKORC1 (-1639A & 1173T) and CYP2C9 genes increased the odds of requiring a lower mean dosage of acenocoumarol. Studying the combination of genotypes in RHD patients could predict acenocoumarol dose requirement more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Among Southeast Asian countries, Vietnamese had close CYP2C9*3 wild-type allele distribution to Thais, Malaysian, Indonesian. However, variant alleles of VKORC1-1173 and -1639 in these countries were in range of 64 to 70 %, lower than that of Vietnamese (85.3 and 92.7 %, respectively) [14,18].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Among Southeast Asian countries, Vietnamese had close CYP2C9*3 wild-type allele distribution to Thais, Malaysian, Indonesian. However, variant alleles of VKORC1-1173 and -1639 in these countries were in range of 64 to 70 %, lower than that of Vietnamese (85.3 and 92.7 %, respectively) [14,18].…”
Section: Discussionmentioning
confidence: 69%
“…These distributions of CYP2C9*3, VKORC1-1173 and VKORC1-1639 allele in Vietnamese population in this study were similar to these of East Asia people, for example Han-Chinese (95; 81.2 and 90 %), Japanese (95.8; 81.9 and 90.3 %), Korea (90.8; 85.5 and 92 %) and Taiwan (95.4; 80.5 and 89.0 %), respectively [18]. However, this prevalence was significantly different with other populations, including South, West and Central Asian, Caucasians, South American where the wild-type allele of CYP2C9*3 (60 -85 %) and variant alleles of VKORC1-1173 and VKORC1-1639 (14 -56 %) were rather lower [14]. Among Southeast Asian countries, Vietnamese had close CYP2C9*3 wild-type allele distribution to Thais, Malaysian, Indonesian.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A few studies from South Indian states have published data regarding the VKORC1 (−1639G>A) rs9923231 polymorphism and its effect on daily warfarin dose requirement 11, 12, 13, 14, 15, 16. Meanwhile, other studies on South Indian populations have also reported allele and genotypic frequencies without accessing association with dosage requirements 17, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%